2020
DOI: 10.1007/s42399-020-00502-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children: Clinical Characteristics and Follow-Up Study

Abstract: Since December 2019, the coronavirus disease 2019 (COVID-19) has spread globally. But the clinical symptoms and detailed follow-up of children with COVID-19 infection are lacking. Here, we conducted a retrospective study including children with confirmed COVID-19. We recorded patients' epidemiological, clinical features, and follow-up data after discharging in order to improve the awareness and treatment of children with COVID-19. Keywords Children. COVID-19-infected. Clinical features. Epidemiological. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…A majority of children contracted the disease from adults in their families. Similar family clustering of pediatric cases has been reported earlier [2][3][4][5]. However, children may get the disease from non-family members also and hence children should also be encouraged to follow precautions at a personal and social level.…”
Section: Discussionsupporting
confidence: 71%
“…A majority of children contracted the disease from adults in their families. Similar family clustering of pediatric cases has been reported earlier [2][3][4][5]. However, children may get the disease from non-family members also and hence children should also be encouraged to follow precautions at a personal and social level.…”
Section: Discussionsupporting
confidence: 71%
“…Much positive changes have happened in child and adolescent health in recent years but children and youth growing up today face new and unprecedented threats to their health [ 14 ]. The COVID-19 pandemic has exacerbated many of these threats, jeopardizing child welfare gains and causing a global economic and health crisis, which will impact children and adolescents in terms of economic disadvantage, health and access to services [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included one case of infection with Aspergillus flavus , one case with Candida glabrata , and three cases with Candida albicans [ 12 ]. Another study reported that patients with COVID-19 showed a higher percentage (8–15%) of secondary infections [ 13 , 14 ]. Koehler et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%